Franz Kafka, estetica in nuce (Materiali di Estetica. Terza serie, 2017)
Kafka’s brief Eintrag, written in February 1906, is firstly understood with respect to its typology and structure, so as to subsequently delineate the aesthetica in nuce that anticipates his more mature aesthetics and poetics.Keywords: Aesthetica in nuce; typology; structure; poetics